Scientific Rationale for The Development of Low-Intensity Irrigation Systems in Azerbaijan - Soltanzade, Qasim Ali oqlu (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2018)
The results of the study revealed that the mismatch intensity rain rate of water absorption into the soil formation of a surface relief and soil erosion, uneven and shallow soaking imperfection open irrigation system at a superficial irrigation, the need for different irrigation methods in the growing and not growing periods, low coefficient land utilization, high cost of irrigation and other features are, to a certain extent in conflict with the requirements of watering cultivated with techniques for / of crops in an area at the deep groundwater.